Effect of macroeconomic on stock market during pandemic / Muhammad Jasyimi Ian Alioefry - Ian Alioefry, Muhammad Jasyimi (2022)
The aim of the study is to explore the relationship during pandemic among selected macroeconomic variables and Malaysia stock market index which is known as Kuala Lumpur Composite Index (KLCI). The stock market and selected macroeconomic variables such as gross domestic product, inflation rate, exchange rate, interest rate and industrial production are taken as independent variables as well as pandemic that taken as dummy variable while stock market is taken as dependent variable. To capture the maximum variation in stock market, time series analysis is done on monthly data from year 2002 to 2020. The pandemic event is only focus happened in Malaysia which is severe acute respiratory syndrome (SARS), influenza a virus subtype (HIND, Middle East Respiratory Syndrome (MERS), Coronavirus disease 2019 (COVID-19). Normality test is employed to test the normality of data. Correlation among the variables tested by correlation test. Then the significance of the explanatory variable is examined within the F-Test framework. Finally, Multiple Linear Regression used to explore the statistical relationship and evaluate the hypothesis in this paper.